Autologous conditioned serum for chronic pain in patients with osteoarthritis: A feasibility observational study. Issue 1 (February 2023) - Ippolito, Mariachiara; Spurio, Giulia; Compagno, Viviana; Rizzo, Alessandra; Di Simone, Marta; Corsale, Anna Maria; Mazzola, Giuseppina; Giarratano, Antonino; Meraviglia, Serena; Cortegiani, Andrea; Alongi, Antonietta
Background: Autologous conditioned serum is a product of blood origin, with fragmented evidence of therapeutic properties in osteoarthritis chronic pain. This pilot observational prospective study aimed to evaluate the feasibility of a treatment with conditional autologous serum (ACS) in patients with severe chronic pain and grade I-III osteoarthritis and to describe its cytokine content. Methods: We prospectively collected data on consecutive patients affected by osteoarthritis grade I to III and treated with four weekly injections of ACS at our outpatient pain service. The primary outcome was pain intensity, measured with the visual analogic scale (VAS). Additional outcomes were symptoms evaluated using joint district-specific scales. The study also evaluated concentrations of 48 cytokines and chemokines involved in the balance pro-inflammation/anti-inflammation and tissue repair in the ACS. Results: We included 26 patients, mostly female (65.4%), with a median age of 63.5 years [IQR 58.25–73]. A median reduction of VAS of −3 cm [−5; −1.25] was observed 6 months after the first injection of ACS. The analysis showed a statistically significant difference between the values of VAS ( p < .01; X 2 = 69.6; df = 6, N = 26) at the different time points. No adverse events were observed or reported by patients during the entire study period. Conclusions: Conditional autologous serum may be a feasible option for patients with chronic pain due to grade I-III osteoarthritis refractory to other treatments. These preliminary findings should be confirmed in studies with adequate design.